All‐oral 12‐week treatment with daclatasvir plus sofosbuvir in patients with hepatitis C virus genotype 3 infection: ALLY‐3 phase III study. Issue 4 (10th March 2015) - Nelson, David R.; Cooper, James N.; Lalezari, Jacob P.; Lawitz, Eric; Pockros, Paul J.; Gitlin, Norman; Freilich, Bradley F.; Younes, Ziad H.; Harlan, William; Ghalib, Reem; Oguchi, Godson; Thuluvath, Paul J.; et al.
Abstract : Treatment options for patients with hepatitis C virus (HCV) genotype 3 infection are limited, with the currently approved all‐oral regimens requiring 24‐week treatment and the addition of ribavirin (RBV). This phase III study (ALLY‐3;ClinicalTrials.gov : NCT02032901) evaluated the 12‐week regimen of daclatasvir (DCV; pangenotypic nonstructural protein [NS]5A inhibitor) plus sofosbuvir (SOF; pangenotypic NS5B inhibitor) in patients infected with genotype 3. Patients were either treatment naïve (n = 101) or treatment experienced (n = 51) and received DCV 60 mg plus SOF 400 mg once‐daily for 12 weeks. Coprimary endpoints were the proportions of treatment‐naïve and treatment‐experienced patients achieving a sustained virological response (SVR) at post‐treatment week 12 (SVR12). SVR12 rates were 90% (91 of 101) and 86% (44 of 51) in treatment‐naïve and treatment‐experienced patients, respectively; no virological breakthrough was observed, and ≥99% of patients had a virological response (VR) at the end of treatment. SVR12 rates were higher in patients without cirrhosis (96%; 105 of 109) than in those with cirrhosis (63%; 20 of 32). Five of seven patients who previously failed treatment with an SOF‐containing regimen and 2 of 2 who previously failed treatment with an alisporivir‐containing regimen achieved SVR12. Baseline characteristics, including gender, age, HCV‐RNA levels, and interleukin‐28B genotype, did not impact virological outcome. DCV plus SOF was well tolerated; there were no adverse events (AEs) leading to discontinuation and only 1 serious AE on‐treatment, which was unrelated to study medications. The few treatment‐emergent grade 3/4 laboratory abnormalities that were observed were transient. Conclusion : A 12‐week regimen of DCV plus SOF achieved SVR12 in 96% of patients with genotype 3 infection without cirrhosis and was well tolerated. Additional evaluation to optimize efficacy in genotype 3–infected patients with cirrhosis is underway. (Hepatology 2015;61:1127–1135)